Ethnosocial processes in Siberia: Topical issues of theory and practice - Popkov, Yuri V. (The New Research of Tuva, 2016)
The article brings together the outcomes of a number of studies conducted by the Novosibirsk school of ethnosociological research and led by the author. For many years, the school has been involved in theoretical and empirical research of ethnosocial processes in Siberia and neighboring regions. In this article, we also make use of an expert survey on assessing the state and trends in ethnosocial developments of peoples of Siberia during the 1990s (Tuva, Khakassia, Buryatia, Altai and Evenk Autonomous Okrug; the survey was held in 1999-2001 and covered 780 participants); expert and mass survey on ethnosocial development and ethnosocial policy held in Khanty-Mansi Autonomous Okrug – Yugra, Novosibirsk Oblast and Altai Republic in 2013-2014 (over 2000 participants); and expert surveys of civil servants on the regional and municipal levels in various regions of the Siberian Federal District (2011-2016, 120 participants were asked to assess the ethnosocial situation in their region and the current ethnonational policy). Ethnosocial processes are to be understood as a system of mutual transformation of ethnosocial subjects in the course of their interaction, rather than as simply a connection between separate social and ethnic processes. Furthermore, ethnosocial processes do not imply transformation only; they feature a balance between changeability and continuity under various guises, including their ‘vertical structuring’ from ethno-environmental and ethno-demographic issues to ethno-political and ethno-legal ones. We have shown that a single ethnosocial process should be described and differentiated by its territorial location, rather than its ethnic or social basis. This allows us to represent the local community in its integrity. As a rule, it is rarely monoethnic, and frequently polyethnic or interethnic. The community develops through interactions between its ethnosocial subjects. Hence, any description of an ethnosocial process should include analyzing the intertwined development of a number of ethnicities (or ethnic groups) that all together make up the local (or regional) interethnic community. By generalizing the outcomes of the empiric studies, we can single out the negative trends in the ethnosocial development of peoples of Siberia in the 1990s. These trends include the return to subsistence farming as the basis of survival, degradation and monoethnization of the countryside, ethnicity-based clustering in urban areas, increased social distance between ethnic groups on the basis of their representation in the institutions of regional and local power, as well as access to social benefits, etc. Contemporary ethnosocial situation in Siberia can be described as a combination of such factors as various degrees of tension in interethnic relations in regions of Siberia, negative dynamics of these relations (although stabilized in last two years), migration as a major factor of tension, lower feeling of social security of permanent population, especially ethnic Russians, as compared to migrants, and the negative attitudes to migrants in host communities. We make a special focus on the role of authorities and their prestige for building the feeling of civil unity and national civic identity.